Mathematics Stack Exchange is a question and answer site for people studying math at any level and professionals in related fields. Join them; it only takes a minute:

Sign up
Here's how it works:
  1. Anybody can ask a question
  2. Anybody can answer
  3. The best answers are voted up and rise to the top

Find limit as h approaches 0 of $$ \frac{e^{x(h+2)^2} - e^{4x}}{h} $$

I know that somehow this is related to me taking the partial derivative of x

I also know $$\frac{\partial f}{\partial x}(x,y) = \lim_{h\to0} \frac{f(x+h,y) - f(x,y)}{h}$$

But I don't know what to do from here.

share|cite|improve this question
up vote 1 down vote accepted

Consider the function $f(x,y) = x y^2 $. Its partial derivative at $y=2$ is given by

$$ \lim_{y \to 2}=\frac{e^{xy^2} - e^{4x}}{y-2}\,.$$

Putting $h=y-2$ transforms the limit to

$$ \lim_{h \to 0}=\frac{e^{x(h+2)^2} - e^{4x}}{h} = \frac{\partial f(x,y)}{\partial y}|_{y=2} =\dots \,. $$

share|cite|improve this answer

I would say, this itself wants to be a derivative of some function. What this function could be? Rather write $\frac{\partial f}{\partial y}$ then it will look more similar. Take $y=2$.

share|cite|improve this answer
sorry. I'm not sure what you mean. – 40Plot Sep 30 '12 at 23:01

You can expand the square $\frac{e^{x(h+2)^2} - e^{4x}}{h}=\frac{e^{(xh^2+4hx+4x)} - e^{4x}}{h}=\frac{e^{xh^2}e^{4xh}e^{4x}-e^{4x}}h$ then use the Taylor series for the exponentials that have $h$ in them.

share|cite|improve this answer

Your Answer


By posting your answer, you agree to the privacy policy and terms of service.

Not the answer you're looking for? Browse other questions tagged or ask your own question.